The Use of Social Media (Twitter) in The Winning of East Java Province Election in 2018 - Prakasita, Ajeng Widya (Indonesian Journal of Political Studies, 2022)
This study aims to look at the use of social media (Twitter) in winning the 2018 East Java Provincial Election. Social media and online media are currently being used by pairs of candidates for the 2018 East Java Pilkada to attract public sympathy. Based on a survey conducted by Indonesia Indicator as of April 2018, media exposure is still dominated by Saifullah Yusuf (Gus Ipul) as a top influencer compared to other candidates. In the 2018 East Java Pilkada, the media also has a big role in shaping public opinion. The author uses the concept of media framing to see how the use of social media (Twitter) in winning the 2018 East Java Pilkada. The method used is a case study as a method that aims to explain how the use of Twitter social media in winning the 2018 East Java Pilkada. We limit this research to see how social media (Twitter) can shape public opinion in the 2018 East Java Regional Head Election. Data collection is done by document analysis and online observation. Document analysis was carried out by looking at the results of the report that had been released by Indonesia Indicator (I2) regarding the media monitoring they carried out during the 2018 East Java Pilkada.